Killer or helper? The mechanism underlying the role of adenylate activated kinase in sound conditioning - Zhao, Rui; Ma, Changhong; Wang, Minjun; Li, Xinxin; Liu, Wei; Shi, Lin; Yu, Ning (Frontiers in Synaptic Neuroscience, 2022)
To detect the protection of the auditory system provided by sound conditioning at 65 dB SPL and 85 dB SPL, as well as to clarify the mechanism by which low-intensity noise protects the auditory system by activating adenylate activated kinase (AMPK). Methods: The 12-week-old CBA mice were randomly separated into 4 groups, each with 24 mice: control, sound conditioning (SC), sound conditioning plus noise exposure (SC+NE), and noise exposure (NE). One cochlea of each mouse was immunofluorescently stained to determine the number of synapses and AMPK activation, while the other cochlea was analyzed by western blot for the expression of phosphorylated adenylate activated kinase (p-AMPK) protein expression. Results: 1. ABR thresholds: There was no significant difference between sound conditioning mice and the control mice. The thresholds of click, 4k, 8k, 16k and 24kHz in the SC+NE groups were significantly reduced compared with the NE group. The animals in the SC group also showed faster recovery to the normal threshold. Meanwhile, 65 dB SPL sound conditioning has a more obvious effect on the auditory protection of the organism. 2. synaptic transmitter release: The number of ribbon synapses in the mice after sound conditioning was not statistically different from the control group; after being exposed to 110dB noise, the ribbon synapses in the SC+NE groups were significantly more than NE group although all the groups showed reduced synapses immediately after the noise exposure. The ribbon synapses of all the groups recovered 14 days after the noise exposure and the SC groups recovered faster than the non-sound conditioning group (p<0.05). 3. AMPK activation: AMPK was highly activated in SC group, and p-AMPK expression was detected. However, after 110dB noise exposure, the strongest protein expression was found in the NE group, otherwise the SC+NE group. Conclusions: Sound conditioning animals were more noise resistant and recovered hearing faster than non-sound conditioning animals. 65 dB SPL sound conditioning offers better hearing protection than 85 dB SPL sound conditioning. Early AMPK activation may protect hearing by increasing ATP storage and reducing the release of large quantities of p-AMPK which helped to inhibit synapse damage.